2015
DOI: 10.1016/j.virol.2015.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Initiation and regulation of paramyxovirus transcription and replication

Abstract: The paramyxovirus family has a genome consisting of a single strand of negative sense RNA. This genome acts as a template for two distinct processes: transcription to generate subgenomic, capped and polyadenylated mRNAs, and genome replication. These viruses only encode one polymerase. Thus, an intriguing question is, how does the viral polymerase initiate and become committed to either transcription or replication? By answering this we can begin to understand how these two processes are regulated. In this rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
132
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(138 citation statements)
references
References 96 publications
(112 reference statements)
4
132
0
Order By: Relevance
“…According to the current paramyxovirus models, both transcription and replication are initiated at the 3= end of the genomic RNA (30). The linear unidirectional organization of the "herringbone" NC means that the 3= and 5= ends of the NC do not present the same molecular surface due to this polarity.…”
Section: Discussionmentioning
confidence: 99%
“…According to the current paramyxovirus models, both transcription and replication are initiated at the 3= end of the genomic RNA (30). The linear unidirectional organization of the "herringbone" NC means that the 3= and 5= ends of the NC do not present the same molecular surface due to this polarity.…”
Section: Discussionmentioning
confidence: 99%
“…A more recently developed nucleoside analogue, marketed by Gilead Pharmaceuticals as Sovaldi, is now the basis of a cure for hepatitis C virus infection (350), with several more promising drugs and preparations in various stages of development. With regard to RSV therapeutic development, a robust in vitro RSV polymerase system (115,117,351) has been used to test nucleoside analogue libraries and other small-molecule inhibitors for their ability to inhibit the RSV polymerase complex. There is one nucleoside analogue named ALS-008176 (4=-chloromethyl-2=-deoxy-3=,5=-di-O-isobutyryl-2=-fluorocytidine) that was discovered using an RSV replicon readout system (352); it underwent successful clinical trials and was reported to inhibit RSV viral load by over 85% in human volunteers (102).…”
Section: Nucleoside Analogues and Small-molecule Inhibitorsmentioning
confidence: 99%
“…The mechanism that drives the very same viral polymerase complex to either mRNA or genome synthesis, a process that ignores all cis-acting transcription start and stop signals encoded by the genome, is poorly understood. For other Mononegavirales, it is suggested that the amount of NP which encapsidates the nascent genomic and antigenomic RNA plays an important role in activating replication (11)(12)(13). It is conceivable that once replication of the viral genome is initiated, transcription and replication run in parallel.…”
Section: Importancementioning
confidence: 99%